The Study of Job Effieiency Internal Organization Factors Affecting Happiness At Work of Muicipal and Hiring Employees of Subdistrict Municipality in Ubon Ratchathani Province - Lamom, Nanthana; Pheunpha, Pichyada (NIDA Development Journal, 2018)
The purposes of this research were 1) to study the level of internal organization factors, job efficacy, and happiness at work between municipal and hiring employees. 2) to examine employee demographics, internal organization factors, job efficacy effecting happiness at work of municipal and hiring employees. Samples were 390 municipal and hiring employees of the sub-district municipality in Ubon Ratchathani province. The Cluster sampling technique and questionnaire with 0.94 of reliability coefficient were used in this research. The data were analyzed by descriptive statistics and multiple linear regression analysis. The research results were as follows: 1) the levels of job efficacy, happiness at work, and internal organization factors were generally high with mean = 3.93, 3.92 and 3.87 respectively. 2) Multiple linear regression results were found that multiple R = 0.80 which means that the correlation coefficient between 15 predictors strongly correlate with happiness at work. The coefficient of explanation of multiple regression model was R2 = 0.63 which means the predictors can explained happiness at work approximately 63%. Factors affecting happiness at work at statistics significant level including personal relationship ( = 0.27), quantity of work ( = 0.19), time ( = 0.18), outcome expectation ( = 0.15), cost of living ( = 0.14), status ( = 0.10), employee’s type ( = 0.11), and environment ( = 0.09) respectively.